ESSENTIAL LEADERSHIP DOMAINS AND STRATEGIES TO ENHANCE LEADERSHIP SKILLS AMONG UNDERGRADUATE MEDICAL STUDENTS: A MIXED METHODS STUDY: Leadership Skills among Undergraduate Students - Abbas, Syed Muslim; Ashar, Abid (Pakistan Armed Forces Medical Journal, 2021)
Objective: To explore medical undergraduate students’ perceptions pertaining to the key domains of leadership and highlight strategies to enhance leadership skills in undergraduate studies.Study Design: Mixed methods study.Place and Duration of Study: Fatima Memorial Hospital College of Medicine & Dentistry, Lahore, from Sep to Oct 2019.Methodology: A total of 207 medical students were recruited from the first and final year by purposive sampling to fill out a structured questionnaire. Three focus group discussions were conducted comprising of twelve students in each group. All focus groups were audio-recorded, anonymized and transcribed verbatim before the analysis by framework analysis technique.Results: Total fifty percent of the first-year students were of the view that ensuring patient safety was an important component of the leadership domain of improving services whereas only 11% responded as critically evaluating as a component of this domain. The themes that emerged pertaining to the strategies to enhance leadership skills included increasing awareness, role models depicting change, cultural challenges, and supplementing existing practices.Conclusions: The validated essential domains of leadership and its associated competencies should be streamlined strategically and prioritized in accordance with the level of training of the undergraduate medical students. A multicentre study is suggested to gather data at the national level which could inform further development of inclusion of leadership domains within undergraduate MBBS curriculum.